2016
DOI: 10.1016/j.jval.2016.08.409
|View full text |Cite
|
Sign up to set email alerts
|

Risk Elements and Drug Utilization in Stroke Patients

Abstract: were on sulfonylureas and 26.4% of controls were on sulfonylureas. ConClusions: The risk factors influencing Cardiovascular Disease in Indian(non-smoking and nonalcoholic ) women with T2DM are advancing age , BMI more than normal ,women on mixed diet, with duration of diabetes and hypertension more than 5 years. Women on Sulfonylureas have more risk of developing cardiovascular disease. There are limited studies reported on primary CV event in Indian diabetic women's associated risk factors comparable to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In the present study, it was found that most of the subjects were hypertensives (62%) which is a major risk factor for development and progression of stroke followed by alcoholics (41%), addicted to smoking (33%) & diabetics (24%) which is in accordance with other studies conducted by Spurthi et.al (2016) 7 , stating that most of the subjects with stroke are hypertensive.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, it was found that most of the subjects were hypertensives (62%) which is a major risk factor for development and progression of stroke followed by alcoholics (41%), addicted to smoking (33%) & diabetics (24%) which is in accordance with other studies conducted by Spurthi et.al (2016) 7 , stating that most of the subjects with stroke are hypertensive.…”
Section: Discussionsupporting
confidence: 92%
“…In general, the study participants consisted of more male than female patients who were 110 (71%) and 45 (29%) patients, respectively. It was found higher in males than females this might be due to the increased stress levels in males and protective estrogen effects in females [7]. Most patients with age more than 60 years old were 81 patients (52%).…”
Section: Discussionmentioning
confidence: 91%
“…Start treatment in patients with ischemic stroke has to be as quickly as possible [6]. Antiplatelet therapy (combination aspirin and clopidogrel) as soon as possible after the even within 24 h can lower the risk for recurrent stroke and functional disability with dual therapy [6][7][8]. The combination of clopidogrel and aspirin as an antiplatelet theraphy is more often used in almost all ischemic stroke patients than other drugs [9].…”
Section: Introductionmentioning
confidence: 99%
“…The other potential approach is neuroprotection strategy. It is trying to impede the ischemic cascade by targeting various components of the cascade that is deemed to be of importance [6].…”
Section: Introductionmentioning
confidence: 99%